Influence Giving Ethanol Extract of Nipah Fronds (Nypa Fruticans Wurmb) on the Lipid Parameters of Male Diabetic Rats of the Wistar Strain - Yuliya Rahma; Danang Raharjo; Bangkit Riska Permata (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diabetes mellitus is gathering disease metabolic with hyperglycemia caused by abnormalities in insulin secretion , insulin action , or both of them . Loss central type 2 diabetes is caused by insulin resistance in muscles and liver as well failure pancreatic beta cells . Purpose This research is to find out How extract ethanol leaf stalk palm affect the lipid values of diabetic rats. Type This research is a experimental . This research is divided into 6 groups with different treatment​ namely normal, control negative CMC-Na (0.5%), control positive glibenclamide (0.45mL), 125mg/kgBW extract , 250mg/kgBW extract and 500mg/kgBW extract . The results of the lipid parameter data were analyzed with SPSS 22 with level 95% confidence level Results study show extract ethanol dose 250 mg/kgBW and 500 mg/kgBW or more Lots lower level total cholesterol , triglycerides , and LDL as well increase HDL levels